2006
DOI: 10.1179/oeh.2006.12.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Middle-aged People Is Associated with Increased Sick Leave: The BELSTRESS Study

Abstract: In a prospective study of the association between self-reported diabetes mellitus and sick leave from work, 21,149 men and women, aged 35-59 years, participated. Prevalence of diabetes was obtained by questionnaire. Sick leave was prospectively obtained from departments of human resources in the year after the baseline survey. Outcome variables related to duration of sick leave, repetitive absences, and long absences of at least seven consecutive days. In gender-specific multivariate analyses the relation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Consistent with previous reports [3][4][5][6][7], our study provides evidence that diabetes is associated with an increase in absence owing to sickness once the disease has been diagnosed. In addition, our findings suggest that this increase predates diabetes diagnosis, as far back as 5-10 years before diagnosis.…”
Section: Period 3 Period 2 Period1supporting
confidence: 94%
“…Consistent with previous reports [3][4][5][6][7], our study provides evidence that diabetes is associated with an increase in absence owing to sickness once the disease has been diagnosed. In addition, our findings suggest that this increase predates diabetes diagnosis, as far back as 5-10 years before diagnosis.…”
Section: Period 3 Period 2 Period1supporting
confidence: 94%
“…In the present study, these diseases were present in <5% of the workers, but they did not influence the risk estimates for LTSA significantly (table 3). Previous studies have reported increased sickness absence rates in people with diabetes compared with diabetes-free subjects (38,39), and CVD has been shown to be responsible for more deaths worldwide than any other condition (40). It could be speculated, that the results of the present study are influenced by a healthy workers effect, suggesting that those with a severe CVD or diabetes might already have left the labor market or shifted to a job with a better match between work demands and individual capacity.…”
Section: Discussionmentioning
confidence: 90%
“…[27][28][29] Our findings show that workers with diabetes leave the labor force prematurely, which has the potential to impose additional costs on employers, including those costs associated with the recruitment and training of new workers.…”
Section: Policy Implicationsmentioning
confidence: 96%
“…All of these health effects might limit workers' functioning and have consequences for career progression; workplace discrimination might also have an impact. 26 Other research has shown that diabetes has a negative effect on workplace functionality, 7 rates of absenteeism, 27 and work productivity. Health might also influence retirement decisions.…”
Section: Discussionmentioning
confidence: 99%